Teplizumab - current state of knowledge on the effects of teplizumab in preventing the development of type 1 diabetes in people at risk - Justyna Białek; Karolina Nitka; Marta Więckowska-Deroń; Monika Leszcz; Dominika Ćwik-Błotnicka; Joanna Borczyk; Martyna Lewkowicz (Kazimierz Wielki University, 2023)
Background and Purpose: Type 1 diabetes is a chronic autoimmune disease from the group of metabolic disorders, where the immune system attacks and destroys the insulin producing cells of the pancreas, leading to hyperglycemia and the need for lifelong exogenous insulin supplementation. This results in increased morbidity, life threatening complications, shortened lifespan and quality of life. So there is an urgent need to develop prevention and treatment for people at risk of developing type 1 diabetes. Current state of knowledge: Recently, there has been significant progress in the field of immunotherapy with therapeutic strategies that focus on stopping the disease in the presymptomatic stage by preserving residual beta-cell function. Randomized, double-blind clinical trials of teplizumab were conducted in relatives of patients with established type 1 diabetes who had not yet been diagnosed with the disease, but were at high risk of developing clinical disease, based on these studies The FDA has approved teplizumab, under trade name Tzield, as a treatment to delay the onset of type 1 diabetes. Conclusion: The reviewed research papers present strong evidence that teplizumab halts the severe decline in beta cells and possibly improves their function after treatment in a high-risk population. In addition, the effect persists.